Penyebab Anemia Pada SLE (Review Sistematic) - Rezwandi Idwar Idrus; Muhammad Hafizh Afriyad Lamusu; Khanza Az-Zahra Baharuddin; Deva Najwa Faisal; Nur Miftahur Rizkah; Nelyan Mokoginta (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Systemic Lupus Erythematosus (SLE) is a multisystem autoimmune disease that is often accompanied by hematological complications, particularly anemia with a high prevalence. This study is a systematic review of journals published between 2019 and 2024 to describe the characteristics of anemia in SLE patients based on age, gender, type of anemia, and severity. Results indicate that anemia most commonly occurs in young adults (20–30 years old) and is more prevalent in women due to the high prevalence of SLE, although men tend to experience more severe disease. AIHA is the most characteristic and high-risk type of anemia, while ACD and IDA are more common in older age groups. The severity of anemia varies from mild to severe, with severe anemia mainly found in AIHA associated with high lupus activity. The most dangerous forms of anemia include AIHA accompanied by thrombotic microangiopathy (TMA) or hemophagocytic lymphohistiocytosis (HLH) because they can cause massive hemolysis and organ failure.